The Relationship between Malaria and Hematological Parameters from Sabya General Hospital, Saudi Arabia - Alanzi, Abdulmajeed Qalil; Almutairi, Rasmia Sabaan; Alanzi, Eman Mohammed; Alshuhri, Bander Mohammed; Mutaen, Ali; Shafeai, Mohammed; Rudiny, Fuad; Banawas, Saeed Saleh; Alenzi, Faris Q.B. (International Journal of Innovative Research in Medical Science, 2024)
Malaria, a disease prevalent in endemic regions, has been found to have significant impacts on hematological parameters, resulting in both direct and indirect effects. These effects have been linked to a considerable number of fatalities. However, certain hematological parameters in populations residing in malaria-endemic areas have yet to be consistently characterized as a benchmark for assessing the prevalence of malaria. This study was designed to evaluate the diagnostic significance of certain hematological alterations in patients infected with malaria, based on the aforementioned fact. The study recruited a sample size of 99 individuals, comprising of 81 patients (cases) who tested positive for malaria and 18 healthy control adults. The male to female ratio in the malaria positive group was 3:1. The findings indicate that among individuals who tested positive for malaria, have low level of hemoglobin and high level of neutrophils. The presence of malaria was significantly linked to leukemia, anemia, and thrombocytopenia, all of which were deemed to be specific indicators for the diagnosis of malaria. The estimation of anemia was found to be specific as well as sensitive for the diagnosis of malaria. Thus, this study indicates that anemia provides the highest diagnostic significance among patients infected with malaria.